Verb categories in Irish Sign Language - McDonnell, Patrick (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 1997)
The principal aim of this study is the identification of verb categories in Irish Sign Language. The data was collected on videotape from six deaf informants, three men and three women, all of whom regard themselves as native signers in Irish Sign Language. In discussing its linguistic properties, we argue that Irish Sign Language is a primary sign language in that it shares the basic structural features typical of other primary sign languages. We show, for example, that handshape, location and movement are key parameters in sign formation and that linguistic constraints determine the acceptability of certain combinations of features in the language. With regard to verb categories in Irish Sign Language, we identify a group of verbs which remain constant in different syntactic contexts, these are plain verbs. Typically, plain verbs are body-anchored signs, tend to occur in semantically related fields, and often express a motivated relationship between form and meaning. Agreement verbs, on the other hand, take affixes which alter the form of the verb in different contexts and which mark for the category of person or for location. Although their surface forms are phonologically similar, person agreement verbs and locative agreement verbs have distinct and prototypical sets of relations with their controller nominals. In a two-tier analysis we show that person agreement verbs associate with the action tier and locative agreement verbs with the thematic tier. We find too, that the semantic roles marked on person agreement verbs map onto grammatical relations such as subject, direct object and indirect object, while roles marked on locative agreement verbs map on to oblique grammatical relations. We identify a further category of verbs which we call classifier predicates of motion and location. Although these verbs can mark for locative agreement they differ significantly from locative agreement verbs; in classifier predicates hand configuration has both a phonological and a morphological function; in locative agreement verbs hand configuration has a phonological function only. Finally, we identify a group of classifier predicates which do not mark for locative agreement but which in other respects are typical classifier predicates. ...
Keywords: Linguistics, Ph.D.; Ph.D. Trinity College Dublin 1997